Anticolitic Effect of the Rhizome Mixture of Anemarrhena asphodeloides and Coptidis chinensis (AC-mix) in Mice - Jang, Se-Eun; Jeong, Jin-Ju; Hyam, Supriya R.; Han, Myung Joo; Kim, Dong-Hyun (Biomolecules & therapeutics, 2013)
During a screening program to search the anticolitic herbal medicines, 80% ethanol extract of the rhizome of Anemarrhena asphodeloides (AA) was found to potently inhibit the expression of proinflammatory cytokines TNF-α and IL-1β, as well as the activation of NF-κB in LPS-stimulated colonic macrophages, followed by that of the rhizome of C. chinensis (CC). AA also potently inhibited TNBS-induced colitic markers, shortening of the colon and increase of macroscopic score, myeloperoxidase activity, TNF-α, IL-1β, and IL-6, in mice. The synergistic effect of CC against the anticolitic effect of AA was investigated. CC synergistically inhibited the anticolitic effect of AA. AC-mix (AA+CC, 1:1) potently inhibited them. AC-mix also inhibited the activation of NF-κB, as well as the expression of TNF-α, IL-1β, IL-6, iNOS and COX-2. The effects of AC-mix against oxazolone-induced colitis were investigated in mice. AC-mix also potently inhibited oxazolone-induced inflammatory markers, colon shortening, macroscopic score, myeloperoxidase activity, NF-κB activation and proinflammatory cytokines. Overall, the anti-colitic effect of AC-mix was superior to that of mesalazine. Based on these findings, AC-mix may improve colitis by inhibiting NF-κB activation.